First Volcanic Plume Measurements by an Elastic/Raman Lidar Close to the Etna Summit Craters - Boselli, Antonella; Scollo, Simona; Leto, Giuseppe; Sanchez, Ricardo Zanmar; Sannino, Alessia; Wang, Xuan; Coltelli, Mauro; Spinelli, Nicola (Frontiers in Earth Science, 2018)
Volcanic emissions represent a well-known hazard mainly for aviation safety that can be reduced with real time observations and characterization of eruptive activity. In order to mitigate risks from volcanic ash, Lidar observations allow to perform immediate and accurate detection of volcanic plumes, quantify volcanic ash concentration in atmosphere and characterize optical properties of volcanic particles, improving modeling of volcanic ash clouds and their potential impact. From 14 to 17 December, 2013, Mt. Etna, in Italy, showed an intense Strombolian activity from the New South East Crater (NSEC). Lidar measurements were performed in Catania, pointing at a thin volcanic plume, clearly visible and dispersed from the summit craters toward the South East. Real-time Lidar observations captured the complex dynamics of the volcanic plume along with the pulsatory nature of the explosive activity and allowed to analyze the geometrical, optical and microphysical properties of the volcanic ash. Both the aerosol backscattering (βA) and the extinction coefficient (αA) profiles at 355 nm, and their ratio [the Lidar Ratio (LR)] were measured near the volcanic source using an Elastic/Raman Lidar system. Moreover, calibrated particle linear depolarization values (δA) were obtained from Lidar profiles measured in the parallel and cross polarized channels at 355 nm, thus allowing to characterize the particle shape. The βA, LR, and δA values were used to estimate the ash concentration (γ) profiles in the volcanic plume. This is the first study of optical properties of volcanic particles through Elastic/Raman measurements near volcanic summit craters and one of few studies which quantify the impact of weak eruptive activity in atmosphere, demonstrating that ash concentration from this type of activity was lower than the safety concentration threshold established by the International Civil Aviation Organization.